LEGAL REVIEW OF GREEN ZONE VIOLATION AT AGRICULTURAL LAND FUNCTIONAL SHIFT ACCORDING TO LOKAL REGULATION KABUPATEN BEKASI NO. 12/2011 OF KABUPATEN BEKASI STAKE LAYOUT PLAN - Iwan Setiyono; Syarif Fadillah; Siti Nur Intihani (Jurnal Hukum Jurisdictie, 2022)
Jurisdictional Review of Green Zone Violations on the Transfer of Agricultural Land Function According to Bekasi Regency Regional Regulation Number 12 of 2011 aims to determine the regulation of land transfer according to Law Number 41 of 2009 on Protection of Sustainable Food Agricultural Land, knowing the transfer of agricultural land function in Bekasi Regency in relation to the arrangement of the Spatial Planning of Bekasi Regency and to determine the legal consequences of the violation of the Transfer of Function of Agricultural Land in relation to not meeting the requirements that have been set. This thesis research uses a normative juridical approach, data sources used, sources and types of data are focused on secondary data that includes legal materials and legal documents including legal cases that are the basis of researchers in order to answer problems and research objectives. Data collection techniques rely on secondary data. The analysis of the data used is done in a qualitative normative manner based on the norms or rules of law and doctrines relevant to the problem. The results of the study showed, First, Bekasi Regency for the improvement of the making of Perda RTRW (Regional Spatial Plan) and the implementation of PERDA No. 12 of 2011 has not been implemented well as seen from the rapid transfer of land functions in Bekasi Regency, this is supported by the lack of public awareness on the importance of sustainable food agricultural land protection, coupled with the lack of repressive action by local governments and law enforcement officers to give effect. jera cause the protection of sustainable food agricultural land is impressed only of a preventive nature. Second, the rapid shift in land function in Bekasi Regency is due to the dynamics of urban growth, demographics and economy, in addition, lack of support for local government policies to maintain agricultural land, weaknesses in regulatory aspects, there is no local regulation regarding thedetailed plan of spatial planning and special regional regulations related to Sustainable Food Agricultural Land (LP2B) so as to open up opportunities for the transfer of agricultural land functions. Therefore, it is necessary to immediately make a spatial map of agricultural land based on GIS (Geographic Information System) as part of maintaining green land in Bekasi Regency.